The Effect Of Perceived Value Towards Purchase Intention Using Information Overload As Moderating Variable In Electric Vehicle - Nur Alif, Noval; Prasetio, Adhi (Publisher Cv. Inara, 2025)
The world of transportation is an important part of this modern era, and technology and innovation in improving the performance of the vehicles we use every day can be useful for increasing the value of activities that depend on this aspect of transportation. Indonesia has started a transition in implementing electric vehicles, one of which is electric cars. Currently, Indonesia has 69,763 electric cars operating on Indonesian roads, but this figure is still very small compared to the Indonesian government's target of 2 million electric cars by 2030. The government has also made this implementation easier with the help of VAT discounts for cars. electricity, but it is still not enough to increase the development of electric cars in Indonesia to achieve the target in the next 6 years. This research aims to determine the influence of Perceived Value or can be interpreted as the value perceived by Indonesian consumers which influences the intensity of buying electric cars. The data collection technique is by distributing questionnaires online to as many respondents as 350 respondents across Indonesia, will be processed and analyzed using the (PLS-SEM) or Partial Least Square Structure Equation model. The finding reveal that perceived value has positive effect on purchase intention through consideration of value in benefits and also risk of EV. additionally, Information overload is negatively affecting the result of perceived value toward purchase intention.